Effect of NiO/YSZ cathode support pore structure on CO2 electrolysis via solid oxide electrolysis cells. Issue 15 (December 2018) - Wang, Tengpeng; Wang, Jingjing; Yu, Libo; Ye, Zhengmao; Hu, Xun; Marnellos, George E.; Dong, Dehua
Abstract: Gas diffusion within supporting cathodes of solid oxide electrolysis cells (SOECs) plays an important role in CO2 electrolysis process. This study has investigated the effect of cathode pore structure on gas diffusion during CO2 electrolysis. The cathode pore structure was adjusted by applying the different amounts of pore former during cathode preparation. The more pore former added produced the higher porosity of cathode and the higher limiting current density. High limiting current densities are beneficial to diminish or even eliminate gas diffusion limitation in practical applications, where the electrolysis is expected to be operated at low CO2 concentrations to increase CO2 conversion. An advanced impedance spectroscopy study is performed to confirm the limiting current density measured according to current-voltage curves. It was revealed that CO2 electrolysis performance is greatly affected by gas diffusion, which is determined by the employed cathode pore structure.